2018
DOI: 10.3390/su10124770
|View full text |Cite
|
Sign up to set email alerts
|

Value Addition and Productivity Differentials in the Nigerian Cassava System

Abstract: There is an increasing need to improve value addition in order to get maximum utility from agricultural systems. Using a retrospective panel data from 482 cassava farmers covering the years 2015–2017, this study examined the effect of value addition on productivity of farmers in the cassava system in Nigeria. We analysed a non-parametric Data Envelopment Analysis to examine productivity across cassava production systems over the three year period. We also examined the impact of value addition on productivity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The finding disagrees with that of Kehinde and Aboaba [37] who reported that the processing experience of cassava processors in Southwest Nigeria is inversely related to value added cassava products. Similarly, Adeyemo and Okoruwa [38] reported that a higher processing experience decreases the prospect of adding value to cassava products. Meanwhile, the finding agrees with that of Okebiorun and Jatto [34] who found processing experience to be significant and positively correlated with the probability of value addition to cassava among women processors.…”
Section: Resultsmentioning
confidence: 94%
“…The finding disagrees with that of Kehinde and Aboaba [37] who reported that the processing experience of cassava processors in Southwest Nigeria is inversely related to value added cassava products. Similarly, Adeyemo and Okoruwa [38] reported that a higher processing experience decreases the prospect of adding value to cassava products. Meanwhile, the finding agrees with that of Okebiorun and Jatto [34] who found processing experience to be significant and positively correlated with the probability of value addition to cassava among women processors.…”
Section: Resultsmentioning
confidence: 94%
“…The main aim of this paper is to examine the impact of agricultural cooperatives on TE of maize production. Previous studies that have estimated technical efficiencies have either used a non-parametric approach such as data envelopment analysis (DEA) [e.g., [ 41 , 42 ]] or a parametric approach such as stochastic production frontier (SPF) model [e.g., [ 18 , 43 ]]. However, the non-parametric DEA approach fails to account for stochastic errors and also attributes the shift from the efficiency frontier to inefficiency [ 44 , 45 ].…”
Section: Conceptual Framework and Estimation Strategymentioning
confidence: 99%
“…In this design, farmers receive agriculture advisory messages in both text and voice.  Framework for value addition and productivity differentials-This framework proposed by (Adeyemo & Okoruwa 2018) is designed to enable the farmers to predict the expected increase in productivity given their decisions to add value to their cropping activities.  Tomato expert system framework-This framework proposed by Dubey, Pandey, & Gautam (2013) provides a general guideline for building crop diagnosis solutions leveraging advancements in technology such as machine learning and artificial intelligence.…”
Section: E-agricultural Framework On Improving Agricultural Productivitymentioning
confidence: 99%